Neutrophil-activating protein in Bacillus spores inhibits casein allergy via TLR2 signaling - Liang, Zhuwei; Zhang, Chao; Liu, Xiaoyu; Yang, Kaiyue; Xiong, Zhile; Liang, Bingshao; Mai, Jialiang; Xiao, Xiaojun; Liu, Jie; Yang, Pingchang; Xu, Damo; Zhou, Zhenwen (Frontiers in Immunology, 2024)
Background: Milk allergy commonly occurs in children, mainly caused by bovine-derived casein (CAS) protein. Neutrophil-activating protein (NAP) of Helicobacter pylori plays an immunomodulatory role with potential to suppress Th2-type immune responses. Bacillus subtilis (B. subtilis) spores are commonly used as oral vectors for drug delivery. Objective: To investigate whether recombinantly expressed NAP on B. subtilis spores could be an effective treatment for CAS allergy in mouse. Methods: After CAS sensitization, mice were orally administered B. subtilis spores expressing recombinant NAP for 6 weeks. Allergic symptoms and parameters were evaluated after CAS challenge oral gavage, including allergic inflammation, splenic cytokines, and serum-specific antibodies. Protein levels of Toll-like receptor 2 (TLR2) and c-JUN in the jejunum tissue were measured by western blot. Bone marrow-derived macrophages (BMDMs) were stimulated with inactivated NAP spores to measure the influence on cytokine profiles in vitro. Results: NAP recombinant spore treatment significantly reduced allergic symptoms and intestinal inflammation. Interleukin-12 and interferon-gamma levels increased, whereas serum CAS-specific IgG1 and IgE levels decreased. TLR2 and c-JUN expression levels were elevated in the jejunal tissue. Inactivated NAP spores polarized BMDMs to the M1 phenotype and enhanced cytokine expression, which were inhibited by a TLR2 neutralizing antibody. Conclusion: NAP offers a new strategy in the treatment of CAS allergy by inhibiting the Th2 response, while eliciting macrophages to promote Th1 immune responses.